EFFICACY OF TOPICAL APPLICATION OF FARGALS IN THE TREATMENT OF SURGICAL SOFT TISSUE INFECTION (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Purulent surgical diseases of the skin, subcutaneous fatty tissue, muscles and fascia occupy a large share among applications for surgical care in outpatient and polyclinic institutions. The purulent process that develops in diabetes tends to spread rapidly, with extensive necrotic process developing . Due to decreased immunity, inflammation often becomes destructive. Mutations of microorganisms lead to the development of antibiotic-resistant forms, which is accompanied by progression and aggravation of the course of diabetes mellitus. Mutations of microorganisms lead to the development of antibiotic-resistant forms, which is accompanied by progression and aggravation of the course of diabetes mellitus. The development of surgical infection in this category of patients runs with various forms of sepsis manifestations. In this regard, it is necessary to start complex treatment from early clinical manifestations, which should include local treatment timely surgical treatment, followed by local management of the wound process. This work is devoted to the study and evaluation of the results of FarGALS drug application in surgical infection in diabetic patients.
Keywords: Diabetes mellitus, surgical infection, purulent wound.